HUBUNGAN ANTARA DOKTER DENGAN PASIEN DALAM PELAYANAN KESEHATAN DILIHAT DARI PERSPEKTIF HUKUM - Imam Mashuda; Agus Pramono (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2019)
The doctor-patient relationship is a pattern that is born between doctors and patients before continuing on health service actions. Health services are a sub-system of health services whose main objective is health services in terms of preventive (prevention), promotive (health improvement), curative (health healing) and rehabilitative (recovery) efforts. excellent and in accordance with standard procedures and standard operating procedures for health services. This service is all efforts deployed by the government in improving the quality of excellent health services and in accordance with the standards of procedures and operational standards of health care procedures. The legal development of doctors and patients as the development of science in the field of health law has changed, originally the position of patients was considered not equal to doctors. Doctors are considered to know the most about their patients, the position of the patient is very passive, which depends on the doctor. This relationship in its development undergoes a change in pattern. The formulation raised in this writing is how the legal relationship between patients and doctors in health services. The research method used is juridical-normative by using the approach of legislation. The result of this study is that the relationship between doctors and patients in health services is equivalent. All medical actions that the doctor will take on his patient must get approval from the patient, after the patient gets a sufficient explanation of all the ins and outs of the disease and the efforts of medical action. The legal relationship between doctors and patients in health services is inseparable and has concrete relevance, so that doctors and patients are an integral part of cooperation in therapeutic transactions. Keywords: Patients, Medical Personnel (doctors), Legal relations.